2011
DOI: 10.1177/1090820x11424149
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Septal Cartilage in Rhinoplasty: Cadaveric Analysis and Assessment of Graft Selection

Abstract: Anatomical variations of the thickness of septal cartilage excisions were found to be statistically significant, and these differences play an important role in the proper selection of the septal grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…They were cut into right-angled, L-shaped pieces, with the long limb measuring 30 mm and the short limb measuring 20 mm to correlate with previous investigations of nasal septal anatomy. 6 Widths of L-strut limbs were carved in a range of 5 to 20 mm. Yield strength in each L-strut was obtained in the same manner as cadaver cartilage, except that the L-struts were held at the distal end of the 2 limbs in the vise grip while the junction of the limbs was compressed.…”
Section: Septal Cartilage Modelmentioning
confidence: 99%
“…They were cut into right-angled, L-shaped pieces, with the long limb measuring 30 mm and the short limb measuring 20 mm to correlate with previous investigations of nasal septal anatomy. 6 Widths of L-strut limbs were carved in a range of 5 to 20 mm. Yield strength in each L-strut was obtained in the same manner as cadaver cartilage, except that the L-struts were held at the distal end of the 2 limbs in the vise grip while the junction of the limbs was compressed.…”
Section: Septal Cartilage Modelmentioning
confidence: 99%
“…As prior research has shown, changing the anatomical constructs of L-struts affects its underlying strength as compared to the unaltered septa. 2,10,12,13 As such, the C-strut concept informs the surgeon, during creation of the cartilage cuts, to arc the incisions posteriorly in a curvilinear fashion, paralleling the natural caudal and dorsal arc to ensure adequate strut width and maximal cartilage harvest. For example, a surgeon working within the L-strut paradigm may adequately estimate the strut width from the ASP but continue a linear cartilage cut that does not adequately provide enough distance from the PCSP.…”
Section: Discussionmentioning
confidence: 99%
“…The thickest part was the septal base anterior to the vomer, which was approximately 2.19-3.03 mm in size, and the thinnest part, at 1.03-1.22 mm, was just above the septal base at 20% of the septal height. Meanwhile, de Pochat et al [10] stated that the average length and height of the septum of a Brazilian sample was 35.4 mm and 32.5 mm, respectively. The thickest part was 1.7 mm and the thinnest part, 1.04 mm.…”
Section: Importance Of Stabilitymentioning
confidence: 99%